Konstruksi Sosial Pendidikan Inklusi: Strategi Pengajaran pada Tiga Sekolah Negeri Jakarta - Simanjuntak, Dian Jesica; Syawaldi, Farhan Pria; Sophia, Fransisca; Rangratu, Ona; Syafiq, Ridho; Anggraeni, Silviana Dwi; Hisyam, Ciek Julyati; Seruni, Mayang Puti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze how inclusive education is socially constructed through teaching strategies implemented in three public schools in Jakarta. Using a qualitative approach and Berger’s theory of social construction, the research explores how inclusive values are expressed, institutionalized, and internalized by educational actors such as teachers, students, and school administrators. The findings indicate that inclusive teaching strategies have begun to take form through flexible learning methods, the admission of students with disabilities, and curriculum adjustments. However, this process still faces several challenges, including limited teacher competence, the absence of support teachers, inadequate facilities, and the lack of a fair assessment system for students with disabilities. On the other hand, school policy support and openness from the school leadership are key factors in encouraging the internalization of inclusive values. This study underscores that inclusive education cannot rely solely on formal policy implementation but requires a continuous social process involving collective participation and awareness from the entire school community to make these values a meaningful part of everyday school life.